2007
DOI: 10.2353/jmoldx.2007.070012
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel One-Tube Isothermal Reverse Transcription Thermophilic Helicase-Dependent Amplification Platform for Rapid RNA Detection

Abstract: The high complexity and cost of polymerase chain reaction-based molecular diagnostics sometimes limits their use in the clinical diagnostics setting. A new helicase-based isothermal amplification method offers an alternative to standard polymerase chain reaction, allowing amplification and detection of specific DNA sequences at a constant reaction temperature without thermocycling equipment. Herein, we describe the development of a novel one-tube isothermal reverse transcription-thermophilic helicase-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 12 publications
(16 reference statements)
0
49
0
Order By: Relevance
“…Nucleic acid amplification through HDA is very robust, and the platform can be applied to both DNA and RNA pathogen amplification. 18,19 We report here the development of the IsoAmp CDAD test using HDA coupled with a simple disposable vertical-flow device, which is designed for instrument-free, cross-contamination-proof detection of amplicons, for rapid identification of toxigenic C. difficile in feces. This assay is based on the amplification of a conserved 5Ј-end fragment of C. difficile tcdA gene.…”
mentioning
confidence: 99%
“…Nucleic acid amplification through HDA is very robust, and the platform can be applied to both DNA and RNA pathogen amplification. 18,19 We report here the development of the IsoAmp CDAD test using HDA coupled with a simple disposable vertical-flow device, which is designed for instrument-free, cross-contamination-proof detection of amplicons, for rapid identification of toxigenic C. difficile in feces. This assay is based on the amplification of a conserved 5Ј-end fragment of C. difficile tcdA gene.…”
mentioning
confidence: 99%
“…We saw the appropriate threshold value increases in our quantitative PCR, but not in our HDA. We accepted these results as real based on literature reports that stated that HDA is not always linear in this respect (Chow et al 2008;Goldmeyer et al 2007Goldmeyer et al , 2008Tong et al 2008). These explanations were not appropriate for the observed discrepancies in our data.…”
Section: Discussionmentioning
confidence: 97%
“…A sensitivity of as few as 10 copies of bacterial genomic DNA has been presented [103]. This thermophilic HDA system was further developed for diagnostic applications by Goldmeyer et al [106,107]. They reported that the HDA is suitable for the rapid …”
Section: Hda: Helicase-dependent Amplificationmentioning
confidence: 99%